2022
DOI: 10.3390/v14030488
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Genetic Characterization of Norovirus Outbreaks That Occurred in Catalonia, Spain, 2017–2019

Abstract: Molecular characterization of human norovirus (HuNoV) genotypes enhances the understanding of viral features and illustrates distinctive evolutionary patterns. The aim of our study was to describe the prevalence of the genetic diversity and the epidemiology of the genotypes involved in HuNoV outbreaks in Catalonia (Spain) between 2017 and 2019. A total of 100 HuNoV outbreaks were notified with the predominance of GII (70%), followed by GI (27%) and mixed GI/GII (3%). Seasonality was observed for GII outbreaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In our study, as expected, the GII genotypes predominated among the infections, in line with several studies performed elsewhere, where norovirus GII detection rates varied from 70% to 93.6% among AGE cases [39][40][41]. During norovirus outbreaks reported in Catalonia, Spain from 2017 to 2019 in closed and semi-closed settings, GII was the predominant genogroup, being involved in 70% of outbreaks [31]. Arowolo et al [42] showed that all norovirus positive samples belonged to GII in a recent study with children below five years old with AGE in Southwest Nigeria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, as expected, the GII genotypes predominated among the infections, in line with several studies performed elsewhere, where norovirus GII detection rates varied from 70% to 93.6% among AGE cases [39][40][41]. During norovirus outbreaks reported in Catalonia, Spain from 2017 to 2019 in closed and semi-closed settings, GII was the predominant genogroup, being involved in 70% of outbreaks [31]. Arowolo et al [42] showed that all norovirus positive samples belonged to GII in a recent study with children below five years old with AGE in Southwest Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study from our group, carried out before the COVID-19 pandemic, has shown the high incidence (32.1%) of norovirus in AGE cases in Brazil, and its high genetic diversity over the period [26]. Globally, few studies have described norovirus epidemiology and genotype circulation during the COVID-19 pandemic [27][28][29][30][31]. Therefore, there is a gap of information concerning the interplay between COVID-19 interventions and the epidemiology of norovirus.…”
Section: Introductionmentioning
confidence: 97%
“…According to the GenBank data, GI.5[P4] was first detected in India in 2016 and was subsequently detected in Brazil, China, South Korea, and Spain between 2018 and 2021. Only one previous outbreak of GI.5[P4] in a nursing home in 2019 affecting 18 individuals has been reported in Spain ( 6 ). In our study, we report a close genetic relationship between all reported GI.5[P4] strains (>99% nucleotide and amino acid similarity), which suggests that this genotype is an emergent virus that has disseminated globally through Asia, the Americas, and Europe within the last 5 years.…”
Section: Epidemiological Investigationmentioning
confidence: 99%
“…Norovirus GI and GII are the leading viral agents for human gastroenteritis, and about 16% of gastroenteritis cases were caused by them [ 7 ]. More importantly, norovirus GII is the leading viral agent in gastroenteritis outbreak [ 8 , 9 , 10 , 11 ]. The economic burden associated with norovirus in societal costs per year was up to USD 60 billion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%